Data and code for "Strong diel variation in the activity of insect taxa sampled by Malaise traps" - Gårdman, Viktor; McDonald, Emme; Roslin, Tomas (Swedish University of Agricultural Sciences, 2025)
Here is presented all data and code used in the article "Strong diel variation in the activity of insect taxa sampled by Malaise traps" by Viktor Gårdman, Emme McDonald & Tomas Roslin.

The sampling of insects through Malaise traps was conducted by the authors. 24 malaise traps were erected in a boreal forest in central Sweden (Lat. 60.024855, long. 17.751336) and emptied every second hour, with the exception of night (samplng events during night = 22:00, 02:00, 06:00) for five consecutive days between 14-19th of July 2022. The sampling design is described in further detail in the article (Fig. 1B). Insects were identified to taxonomic Family for Diptera, Coleoptera, and Hymenoptera, except for the superfamilies of Chalcidoidea and Cynipoidea (Hymenoptera). Chalcidoids and Cynipoids were only identified to the superfamily level, due to difficulties in assigning lower taxonomic levels without risking misidentification. Hemiptera was divided into taxonomic families for Heteroptera, and into suborders for Auchenorrhyncha and Sternorrhyncha. To simplify identification of a large group with similar morphology, all microlepidopteras were grouped as such with no further identification. Furthermore, to speed up the identification task, all insects not belonging to Diptera, Hymenoptera, Coleoptera, Lepidoptera or Hemiptera were identified to Order alone.

The HRS_SpeciesData file contains information about each captured individual across all taxa for each 2 hour sampling interval during the five days of sampling. Dates are given as DD/M. TrapID refers to which of the 24 traps used the individual was found in. Time is given in hh:mm and refers to the time of sampling, Time_con refers to time in only hh, and time_Num shows time of day as a fraction between 0 (00:00) and 1 (23:59). The superfamily belonging for each taxon used is given. Note that for taxa were only taxonomic Order or Suborders are given, the superfamily column refers to this Order or Suborder.

The HRS_EnviData file contains information about how many individual were captured at each timestep for the 17 most common taxa (appearing as >49 individuals or in >19 timesteps), along with weather covariates for each timestep. The weather covariates are average values from the five half hour measurements per sampling period (expect for 22:00-02:00 and 02:00-06:00 where n=9). The taxonomic columns follow the same principle as in HRS_SpeciesData, with an additional column of taxonomic Order. Times and date also follow the same principle as in HRS_SpeciesData. ID is a unique mix of Date and time, given as DDHH (Date, Hour). The emptying of trap at 20:00 on the 15h would have ID 1520. Temperature is given in degrees Celsius (°C), wind speed in m/s, cloud cover as a fraction between 0 (no cloud) and 1 (complete cloud cover), rain in mm, wind direction in cardinal directions, and relative humidity in %. Data on weather covariates was provided by the Swedish Transport Administration (https://www.trafikverket.se/) from weather station 327 Björklinge (Lat. 60.05042, long. 17.62149).

All code was created using R version 4.4.0 and is presented through Rmarkdown

Här presenteras all data och kod för artikeln "Strong diel variation in the activity of insect taxa sampled by Malaise traps" av Viktor Gårdman, Emme McDonald & Tomas Roslin.

Provtagningen av insekter har utförts av författarna . 24 Malaisefällor sattes upp i en boreal skog i centrala Sverige (Lat. 60.024855, long. 17.751336) och tömdes varannan timme under fem dagar, med undantag för nätter (22:00-06:00), som hade ett interval på fyra timmar (tömning 22:00, 02:00, 06:00). Malaisefällornas position i förhållande till varandra illustreras bäst via Fig. 1B i artikeln. Insekterna identifierades till taxonomisk familj för flugor (Diptera), skalbaggar (Coleoptera) och steklar (Hymenoptera). Överfamiljerna Chalcidoidea och Cynipoidea inom Parasitsteklar (Parasitica; Hymenoptera) identifierades enbart till överfamilj på grund av svårigheter med att familjebestämma arter inom dessa överfamiljer. Halvvingar (Hemiptera) bestämdes till familj inom skinbagggar (Heteroptera), men enbart till underordning för stritar (Auchenorrhyncha) och växtlöss (Sternorrhyncha). För att förenkla bestämningsprocessen så gjordes ingen vidare identifiering av småfjärilar (microlepidoptera) och för alla insektsordningar förutom Coleoptera, Diptera, Hymenoptera, Hemiptera och Lepidoptera identifierades arter enbart till ordning.

Filen "HRS_SpeciesData" innehåller information om varje individ som fångades under provtagningsperioden. Det inkluderar datum för fångsten ('Date', givet som DD/M); vilken fälla som individen hittades i (TrapID); tid i hh:mm (Time); tid i enbart timmar (Time_con), tid som en fraktion mellan 0 (00:00) och 1 (23:59) (Time_Num); superfamilj för varje taxon (Superfamily); taxon som varje individ delats in i (Taxon). För taxon med högre taxonomisk nivå än superfamilj anges den taxonomiska nivån i kolumnen för superfamilj.

Filen "HRS_EnviData" innehåller information om hur många individer per taxon som fångades vid varje provtagningstillfälle för de 17 mest frekventa taxa (förekommande som fler än 49 individer eller vid mer än 19 provtagningstillfällen), summerat över alla fällor. Kolumnerna "Taxon" och "Superfamily" följer samma princip som ovan, men här finns även en kolumn för taxonomisk ordning (Order). Kolumnerna för tid och datum följer samma princip som ovan. Kolumnen "ID" är en unik kombination av datum och tid anget som DDhh. T.ex tömningen 20:00 den 15:e har ID 1520. Utöver abundansen av individer för varje ID och taxa ges vädervariabler. Temperatur anges i grader Celsius (°C), vind i meter per sekund (m/s), molntäcke (cloud cover) som en fraktion mellan 0 (klar himmel) och 1 (totalt molntäcke), regn i mm, vindriktning i väderstreck och relativ luftfuktighet i %. Värdena är medelvärden från fem mätningar varje halvtimme från den förra provperioden till nästa, med undantag för nätter där medelvärden kommer från nio halvtimmesmätningar per tömning (tömning 22:00, 02:00, 06:00). Väderdatan kommer från väderstationen 327 Björklinge (Lat. 60.05042, long. 17.62149) och tillhandahålls av Trafikverket (https://www.trafikverket.se/).

All kod är skriven in R version 4.4.0 och presenteras via Rmarkdown
Data och kod för "Strong diel variation in the activity of insect taxa sampled by Malaise traps"
Keywords: air temperature; lufttemperatur; abundance; air relative humidity; community composition; arthropods; Species distribution; Arters utbredning; day; dag; cloud cover; night; wind speed; Diptera; tvåvingar; Lepidoptera; fjärilar; Hemiptera; halvvingar; Plecoptera; bäcksländor; Thysanoptera; tripsar; Neuroptera; nätvingar; Psocoptera; stövsländor; Hymenoptera; steklar; Coleoptera; skalbaggar; diel rythm; dygnsrytm; Malaise trap; Malaisefälla; Ecology; Ekologi; Biota; Biologi och ekologi